Real-Time Imaging with the O-Arm for Skull Base Applications: A Cadaveric Feasibility Study - Raza, Shaan M.; See, Alfred P.; Lim, Michael (Journal of Neurological Surgery Part B: Skull Base, 2012)
Introduction Although intraoperative imaging/navigation has established its critical role in neurosurgery, its role in cranial base surgery is currently limited. Due to issues such as poor bony resolution and accuracy, surgeons have to rely on anatomic landmarks that can be distorted by pathology when drilling out critical structures. Though originally developed for spinal application, we hypothesized that the O-Arm could address the above issues for use in cranial base procedures.Methods A cadaveric study was performed in which heads underwent a preprocedure scan via the O-Arm, a fluoroscopic device capable of providing three-dimensional images through the use of cone-beam technology. Preprocedure scans were taken and then registered to a Stealth S7 machine (Medtronic, Inc., Minneapolis, MN, USA). Key cranial base landmarks were identified on these scans and then subsequently identified under direct visualization after (1) endoscopic endonasal dissection and (2) a middle fossa approach. We then quantified the difference in distance between the preplanned and identified structure during surgery. This difference was considered the error.Results For anterior cranial fossa structures, the mean error was 0.25 mm (anterior septum), 0.27 mm (left septum), and 0.32 mm (right septum). For middle fossa structures, the errors were: 0.11 mm (foramen spinosum), 0.44 mm (foramen rotundum), and 0.21 mm (foramen ovale).Conclusion Based on this preliminary cadaveric study, we feel the O-Arm can provide the necessary imaging resolution at the skull base to be employed for intraoperative navigation during cranial base approaches (open and endoscopic). This study warrants further investigation into its clinical use in patients undergoing similar surgical procedures.
Keywords: intraoperative navigation; O-Arm; skull base